Decoding Class Clashes and Society through Marxist Criticism in the Dystopian Novel The Hunger Games - KOURINI ,Bouchra; HALMOUS ,Samira; Boumous, Moufida (University of Ammar Theledji -Laghouat, 2020)
Suzanne Collins’s The Hunger Games trilogy narrates the post-apocalyptic nation of Panem, the Capitol, and its thirteen districts. Marxism basically deals with the struggles of poor and working class against rich people of society, and socio-economic effects of their struggles on society. In The Hunger Games supreme power of capitol over all districts is the prominent fact of Marxism. In three chapters, this study examines The Hunger Games to highlight the aspects of dystopia by applying the Marxist and the Capitalist theories. This young adult dystopian novel is considered one of the main significant literary works that succeed to reflect the gloomy picture of the present society. This study aims to deeply explore and analyze themes of totalitarian regimes that create dystopia